Measurement, "scriptural economies, " and social justice: governing HIV/AIDS treatments by numbers in a fragile state, the Central African Republic (CAR). Issue 1 (3rd February 2016) - David, Pierre‐Marie
Abstract: Fragile states have been raising increasing concern among donors since the mid‐2000s. The policies of the Global Fund to fight HIV/AIDS, Malaria, and Tuberculosis (GF) have not excluded fragile states, and this source has provided financing for these countries according to standardized procedures. They represent interesting cases for exploring the meaning and role of measurement in a globalized context. Measurement in the field of HIV/AIDS and its treatment has given rise to a private outsourcing of expertise and auditing, thereby creating a new form of value based on the social process of registration and the creation of realities produced by the intervention itself. These "scriptural economies" must be questioned in terms of the production of knowledge, but also in terms of social justice. Governing HIV/AIDS treatments by numbers in a fragile state is explored in this article through the experience of the Central African Republic (CAR) in terms of epidemiology and access to antiretroviral drugs. The unexpected effects of performance‐based programs in this context underline the need for global health governance to be re‐embedded into a social justice framework.